A report of the huge and complex burrow system of the gebiidean mud shrimp Laomedia sp. (Crustacea: Laomediidae) in Korean intertidals - Jaehwan Seo; Bon Joo Koo (Scientific Reports)
Abstract We introduce an account of the unique burrow systems of Laomedia sp. and compare their structures between the environmentally distinct Saemangeum and Gomso tidal flats. Laomedia sp. burrows are characterized by the merging of two branched galleries into a main gallery, spiral structures, and large-volume chambers. These unique structures, not found in other gebiideans, are attributable to the species’ ecological characteristics, wherein a male and female pair cohabit within a single burrow. The upper part of the burrow consists of a horizontal gallery and a vertical shaft connected to the surface. Several horizontal galleries merge into two branched galleries, which then merge into the main gallery, collectively making up the middle part of the burrow. The main gallery is skewed obliquely, spiraling with regular directional changes and extending downward, maintaining a consistent twist direction. Bulging chambers (maximum volume, 590 cm3) are located where the main gallery twists into a spiral. The maximum depth, surface area, and volume of burrows differed between tidal flats: 145 cm, 16,180 cm2, and 18,163 cm3 at Saemangeum and 198 cm, 12,267 cm2, and 10,325 cm3 at Gomso, respectively. This variation is likely caused by the flats’ differing tidal conditions and sediment characteristics. Laomedia sp. burrows increase the sediment–water interface by up to 1,511%, the most observed among marine invertebrate burrows. This study reports to identify the unique burrow systems of Laomedia sp., the largest and morphologically complex among the gebiidean group.